Role Of Service Quality On Organizational Performance Among Telecommunication Employees In Southwestern States In Nigeria - Adeshina Akinwumi Ojo (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The present study examined the role of service quality on organisational performance among telecommunication employees. A survey research design was used to conduct this study with a sample of 123 employees selected using a two-stage sampling technique in Lagos (62 participants and Oyo state (61 participants). Data collection was through a self-reported questionnaire that measured service quality and organisational performance. Results indicate that there exists a significant positive relationship between service quality and organizational productivity of the Nokia telephone company (r = .34; P<.01).service quality had significant joint influence on organizational productivity [R = .54; R² = .29; F (1, 121) = 13.21; P<.01]. The study concluded that service quality predicts organisational performance. The study, therefore, recommended that quality in service delivery be boosted by adding more value-added extra services to customers. This will give the customers the view that Nokia management values their customers.